2016
DOI: 10.1088/0957-4484/27/28/285601
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin hitchhiking on polymer nanoparticles

Abstract: The control of microbial infections is critical for the preparation of biological media including water to prevent lethal septic shock. Sepsis is one of the leading causes of death in the United States. More than half a million patients suffer from sepsis every year. Both gram-positive and gram-negative bacteria are responsible for septic infection by the most common organisms i.e., Escherichia coli and Pseuodomonas aeruginosa. The bacterial cell membrane releases negatively charged endotoxins upon death and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Direct removal of endotoxins from the blood using polymers or magnetic nanocarriers is considered to be an essential tool to improve the patient's health . Polycaprolactone nanoparticles have also been applied for endotoxin removal in water by direct binding …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct removal of endotoxins from the blood using polymers or magnetic nanocarriers is considered to be an essential tool to improve the patient's health . Polycaprolactone nanoparticles have also been applied for endotoxin removal in water by direct binding …”
Section: Resultsmentioning
confidence: 99%
“…Such compounds are continuously released at high concentrations in serum and culture media during bacterial growth and proliferation. [24] In ap revious study,o ur group also observed that the micromotors possess am icroporous structure and that endotoxins can penetrate these structures and also interact with the micromotor by adsorption. [22] Most importantly,s epsis is mainly caused by endotoxins through activation of the immune system.…”
Section: Bacterial Endotoxin Removal With Visible-light-driven Qd/ Fementioning
confidence: 99%
“…PCL NPs were synthesized by the solvent evaporation method which utilized high–speed homogenization and sonication, followed by solvent evaporation, centrifugation to remove surfactants, and then lyophilization 5458 . A PCL solution at a concentration of 10 mg/ml in ethyl acetate was injected using a syringe pump to a 1% w/v polyvinyl alcohol (PVA) solution prepared with reverse osmosis (RO) water.…”
Section: Methodsmentioning
confidence: 99%
“…Endotoxin contamination can mask the true biological effects of nanoparticles and change the distribution and clearance of nanoparticles in the body. [191][192][193][194][195][196] The acute toxicity due to endotoxin and endotoxin-contaminated nanoparticles is primarily manifested by the cytokine release syndrome. The exaggeration of endotoxin-mediated inflammation by certain nanomaterials is a well-documented problem.…”
Section: Importance Of Endotoxin Screeningmentioning
confidence: 99%